Duration of Hormonal Contraception and Risk of Cervical Cancer - Kusmiyati, Yuni; Prasistyami, Annisaputri; Wahyuningsih, Heni Puji; Widyasih, Hesty; Adnani, Qorinah Estiningtyas Sakilah (Kesmas, 2019)
The use of long hormonal contraceptives can disrupt the balance of estrogen in the body, resulting in abnormal cell changes. This study aimed to determine a correlation between the duration of hormonal contraception and risk of cervical cancer. This study used a case-control design. The population were patients who had examined at a cancer installation and obstetrics-gynecology polyclinic Dr. Sardjito Hospital in 2018. Case samples were 95 women have cervical cancer diagnosis and control were 95 women with a negative pap smear. Sampling with random sampling. Dependent variable cervical cancer and independent variable the duration of hormonal contraception are obtained from medical records. Cervical cancer is assessed by doctor’s diagnosis. Data analysis used logistic regression. Results showed that 44.7% of samples used long-term hormonal contraception (over 5 years). Length of use of hormonal contraception had a significant correlation with the incidence of cervical cancer (p-value < 0.01). Hormonal contraceptive use more than 5 years have a risk 4.2 times (95% CI 1.01-5.69) of cervical cancer than using less than 5 years after being controlled with the first marriage age and parity